A retórica de Kant 2 Receptividad y recepción - Rojas Peralta, Sergio E. (2006)
The paper treats the relation between pragmatics and discourse in Kant, and it shows the basic idea for the Criticism: the receptivity. The model of reception in Kant is ambigous: the sensibility is passive and receptive, but Kant don’t explain what means “to receive”. And that is important, because the receptivity defines the condition of things and phaenomena. However, Kant don’t define the system of reception.